Framing Good Food: Communicating Value of Community Food Initiatives in the Midst of a Food Crisis - Knezevic, Irena (Frontiers in Communication, 2021)
Community-embedded food initiatives exist in market economies, but make more-than-market contributions. They challenge the dominant, industrialized food system, while generating non-monetary benefits in their communities. Yet food policy, regulation, and public spending in much of the world is still framed by the values of market economy. Revenue, yield, and technological advancements remain key formal measurements of the wellbeing of food systems. Community-embedded food initiatives like small local businesses and non-profit organizations, are often committed to advancing social and environmental benefits of non-industrialized food, and they call for clearer recognition of their more-than-market contribution to community wellbeing. The Nourishing Communities network has worked with such initiatives for more than a decade, undertaking community-engaged research with practitioners across sectors. The network has found that these initiatives are impeded by a communication conundrum. On the one hand, they are expected (by funders, governments, and other institutions) to demonstrate their value using market-economy measurements and translating what they do into “social returns on investment”. On the other hand, many of those initiatives need non-market terminology to express the values that they espouse and generate. To balance these needs, Gibson-Graham’s framing of “diverse economies” can potentially offer a pathway to better communication and thus more accurate valuing of the work of such initiatives. Their notion of diverse economies offers endless opportunities to frame community food work as valuable in ways that go beyond market-economy measurements. As such, the diverse economies framing offers new possibilities for alternative food, and for more general discussions of social reform.